2017
DOI: 10.15345/iojes.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Primary School Teachers’ Goal Orientations for Teaching

Abstract: This study aims to investigate what Turkish primary school teachers' goal orientations are in the teaching environment, how these goal orientations are correlated with one another and whether teachers' gender and teaching experiences make a significant difference. A relational survey method was used in this study. The participants consisted of 191 primary school teachers working at state schools in Nevşehir, Turkey. The "Goal Orientation Scale for Teaching", developed by Butler (2007) and finalized by Butler a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…This also points out that participant teachers do not ignore the problems they face in their professional lives and when they try to solve them, they feel successful. The results observed in other studies in the literature support current results (Han, Yin & Wang, 2015Retelsdorf & Gunther, 2011;Saban & Yıldızlı, 2017;Yıldızlı et al, 2016).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 91%
See 3 more Smart Citations
“…This also points out that participant teachers do not ignore the problems they face in their professional lives and when they try to solve them, they feel successful. The results observed in other studies in the literature support current results (Han, Yin & Wang, 2015Retelsdorf & Gunther, 2011;Saban & Yıldızlı, 2017;Yıldızlı et al, 2016).…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 91%
“…Teachers with mastery goal orientation, for example, tend to build good relationships with students, support their students more in their learning experiences, and thereby contribute to their social-emotional growth (Butler, 2012). In other researchs on the goal orientation of teachers, a weak and positively significant correlation between ability approach and work avoidance was observed (Butler, 2007(Butler, , 2012Yıldızlı et al 2016, Saban & Yıldızlı, 2017. Butler (2007) claimed that current condition is peculiar to teachers, unlike other studies conducted with students, and it is related to the ability approach, although there is no relation between the work avoidance and teachers' positive teacher orientations such as mastery and student relations.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been observed that the opinions of teachers between 6-10 years are lower than those with other professional seniority (Table 1). Saban and Yıldızlı (2017) found that teachers with 1-5 years of professional seniority had a higher attitude towards goal orientation than teachers with 6-10 years of professional seniority. Teachers with 6-10 years of professional seniority were higher than teachers with 11-15 years of teaching experience.…”
Section: Discussionmentioning
confidence: 87%